2005
DOI: 10.1590/s0100-879x2005000800015
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Staphylococcus aureus and Salmonella enteritidis in tryptic soy broth and caviar samples by high pressure processing

Abstract: We studied the action of high pressure processing on the inactivation of two foodborne pathogens, Staphylococcus aureus ATCC 6538 and Salmonella enteritidis ATCC 13076, suspended in a culture medium and inoculated into caviar samples. The baroresistance of the two pathogens in a tryptic soy broth suspension at a concentration of 10 8 -10 9 colony-forming units/ml was tested for continuous and cycled pressurization in the 150-to 550-MPa range and for 15-min treatments at room temperature. The increase of cycle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…Similarly to other studies, an increase in pressure and holding time of treatments caused higher S. aureus inactivation (Cebri an et al, 2010;Fioretto, Cruz, & Largeteau, 2005;Jofr e et al, 2010;O'Reilly, O'Connor, Kelly, Beresford, & Murphy, 2000). Furthermore, O'Reilly et al (2000) and Fioretto et al (2005) reported identical inactivation for the non-enterotoxic strain (ATCC 6538). Differences in inactivation by HPP between various S. aureus strains are also described in studies of Alpas et al (1999) and Cebri an et al (2010).…”
Section: Discussionsupporting
confidence: 79%
“…Similarly to other studies, an increase in pressure and holding time of treatments caused higher S. aureus inactivation (Cebri an et al, 2010;Fioretto, Cruz, & Largeteau, 2005;Jofr e et al, 2010;O'Reilly, O'Connor, Kelly, Beresford, & Murphy, 2000). Furthermore, O'Reilly et al (2000) and Fioretto et al (2005) reported identical inactivation for the non-enterotoxic strain (ATCC 6538). Differences in inactivation by HPP between various S. aureus strains are also described in studies of Alpas et al (1999) and Cebri an et al (2010).…”
Section: Discussionsupporting
confidence: 79%
“…Various terms have been used to define multi-pulsed HHP treatment, such as oscillatory pressurization and pressure oscillation (Hayakawa, Kanno, Masaaki & Fujio, 1994;Hayakawa, Kanno, Yoshiyama & Fujio, 1994;Kingsley, Guan, Hoover, & Chen, 2006;Palou, López-Malo, Barbosa-Cánovas, Welti-Chanes, Davidson & Swanson, 1998;Yuste et al, 2001), reciprocal pressurization (Furukawa, Nakahara, & Hayakawa, 2000;Furukawa, Shidoma, & Hayakawa, 2003), double treatment (Gola et al, 1996), intermittent treatment (Ponce, Pla, Capellas, Guamis, & Mor-Mur, 1998), interrupted treatment (Masschalck, García-Graells, Van Haver, & Michiels, 2000), dynamic pressure (Koseki & Yamamoto, 2007), discontinuous pressure (Goodridge, Willford, & Kalchayanand, 2006) cycling and cycled pressure (Bradley et al, 2000;Fioretto et al, 2005;Luscher, Balasa, Fröhling, Ananta & Knorr, 2004;Mills, Earnshaw, & Patterson, 1998;Rigaldie, Largeteau, Lemagnen, Demazeau, & Grislain, 2007;Rivalain et al, 2012), multiple-cycle (Del Olmo, Morales, Ávila, Calzada, & Nuñez, 2010Morales, Calzada, Ávila, & Nuñez, 2008;Morales, Calzada, Rodríguez, De Paz, & Nuñez, 2009), pulse(d) or step-pulse(d) pressure, and pressure pulsing (Ahn & Balasubramaniam, 2007;Alemán et al, 1996Alemán et al, , 1998Bari, Ukuku, Mori, Kawamoto, & Yamamoto, 2008;Basak & Ramaswamy, 2001;Basak, Ramaswamy, & Piette, 2002;Buzrul, Largeteau, Alpas, & Demazeau, 2008a;Donsì, Ferrari, & Maresca, 2007;Donsì et al, 2010;…”
Section: Terminology and Types Of The Treatmentmentioning
confidence: 99%
“…Albeit many studies on the inactivation of different bacterial pathogens such as Salmonella, E. coli, and Staphylococcus (Garcia-Graells et al 1999;Fioretto et al 2005;Jofre et al 2010;Lee and Kaletunc 2010;Hereu et al 2012) with various HHP treatments exist, to date, no research on inactivation of Shigella by HHP has been reported in the literature. Other researchers (Hugas et al 2002) treated marinated beef loin by HHP using 600 MPa for 6 min and achieved a 4 log 10 cycle reduction in aerobic, psychrophile, and lactic acid bacterial counts.…”
Section: Discussionmentioning
confidence: 99%